Elephant and Piggy Like Reading! : It's a Sign! - Pumphrey, Jarrett; Pumphrey, Jerome; Willems, Mo (New York : Hyperion Books for Children, 2022)
One, Two, Kat, and Four want to form a club so together they figure out how to make a sign saying what their club should be called.
Keywords: Cooperativeness -- Juvenile fiction; Friendship -- Juvenile fiction; Clubs -- Juvenile fiction; Writing -- Juvenile fiction; Problem solving -- Juvenile fiction; Cooperativeness -- Fiction; Friendship -- Fiction; Clubs -- Fiction; Writing -- Fiction; Problem solving -- Fiction; Humorous stories; Children's book